2014
DOI: 10.1182/blood-2014-06-582346
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of rituximab in adult immune thrombocytopenia: results from a prospective registry including 248 patients

Abstract: Key Points• Tolerance of rituximab is acceptable in ITP, and with its benefit/risk ratio may remain a valid option for treating ITP in adults.We conducted a prospective multicenter registry of 248 adult patients with immune thrombocytopenia (ITP) treated with rituximab to assess safety. We also assessed response and predictive factors of sustained response. In total, 173 patients received 4 infusions of 375 mg/m 2 and 72 received 2 fixed 1-g infusions 2 weeks apart. The choice of the rituximab regimen was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 32 publications
5
138
6
Order By: Relevance
“…It has been reported that younger age was associated with better response (Khellaf et al, 2014). A meta-analysis of studies of non-splenectomized patients receiving rituximab confirmed that younger age was the most relevant predictive factor of response in multivariate analysis (Auger et al, 2012).…”
Section: Rituximabmentioning
confidence: 81%
See 2 more Smart Citations
“…It has been reported that younger age was associated with better response (Khellaf et al, 2014). A meta-analysis of studies of non-splenectomized patients receiving rituximab confirmed that younger age was the most relevant predictive factor of response in multivariate analysis (Auger et al, 2012).…”
Section: Rituximabmentioning
confidence: 81%
“…A meta-analysis of studies of non-splenectomized patients receiving rituximab confirmed that younger age was the most relevant predictive factor of response in multivariate analysis (Auger et al, 2012). Rituximab may be associated with better response in the early stages of the disease (Khellaf et al, 2014). Some studies reported that the response could be better in females (Godeau et al, 2008;, but conflicting results have been reported (Auger et al, 2012;Patel et al, 2012;Khellaf et al, 2014).…”
Section: Rituximabmentioning
confidence: 92%
See 1 more Smart Citation
“…221 New innovative therapies have been successfully introduced and have questioned current therapeutic strategies and stimulated expert discussions. 222,223 Despite the relative rarity of FNAIT, several important advances have been made in the past ten years. Firstly, new diagnostic methods, including fetal genotyping on maternal blood samples and antibody detection using aptamers or recombinant peptides, have been developed and are gradually being introduced into clinical practice.…”
Section: European Research Contributionsmentioning
confidence: 99%
“…Of the available therapies, rituximab was not used as it is slow to act and also, there is a high risk of infections 7 . Of the two available pulse therapies (methylprednisolone and IVIg), IVIg was preferred as it has shown superior efficacy to raise platelet counts in the short term and, it has a better residual effect to maintain the platelet levels 8 .…”
Section: Discussionmentioning
confidence: 99%